The Semantic Shift Of Place In The Cinematic Film (The film “Platform” is an example) - Saad Nadhom Issa (الاكاديمي)
This research is concerned with studying the semantic shift of place in the cinematic film, in order to determine the new semantic and aesthetic dimensions that the shift of place from the ordinary adds. This process can only be done by demolishing the usual structure of the elements (or element) of cinematic expression, taking into account giving one of these The elements dominate the rest of the other elements, in order to create a new structure that expresses the content of the topic’s message. The research included the following: Chapter One: The problem of the research, its importance, the need for it, its goal and its limits, mentioning the name of the sample, then defining the terms to provide the procedural definition of the research. Chapter Two: It includes three topics: The first - the concept of displacement and its historical root. Second: The significance of place in literature and art. Third: Representations of the operation of the semantic shift of place in the film. It ended with indicators of the theoretical framework and previous studies. Chapter Three: Research Methodology. Chapter Four (Results and Conclusions): Results: